The Effect of Rice Fermented (Tape Ketan Hitam) Liquid Fraction Concentrations and Incubation Times on pH, Viscosity and Organoleptic Quality of Goat Milk - Naili Iqrimah; Purwadi Purwadi; Lilik Eka Radiati (Jurnal Ilmu dan Teknologi Hasil Ternak (JITEK), 2013)
This study aimed to determine of interaction and the best of percentage rice fermented liquid fraction addition and incubation times on pH, viscosity and organoleptic quality. The experimental method was designed by factorial Completely Randomized Design (CRD) which three times replicated. The treatment consists of rice fermented liquid fraction concentrations by 5 %, 15 %, 25 % and 35 % (v/v)Â  and incubation times by 0 (without incubation) , 8,16 and 24 hours. The results showed that the different concentration of rice fermented liquid fraction showed a significantly different effect on pH, viscosity, colour, smell, taste and textur, whileÂ  in incubation times gave a significantly different effect on pH, viscosity, smell, taste and textur but not give a significant effect on colour. The best combination obtained from addition of rice fermented liquid fraction 25 % and 24 hours of incubation times.Key words: goat milk, rice fermented liquid fraction, incubation times